Characterization of free fatty acids photo‐oxidation under UV radiations: A stepwise Raman study. (12th September 2022) - Assi, Ali; Michael‐Jubeli, Rime; Baillet‐Guffroy, Arlette; Tfayli, Ali
Abstract: Lipid peroxidation (LPO) is an oxidative deterioration when oxidants such as reactive oxygen species attack lipids that contain double bonds especially polyunsaturated fatty acids (PUFAs). The mechanism of LPO is composed of three steps: initiation, propagation, and termination. It can result from several reaction pathways: (1) auto‐oxidation, (2) enzymatic oxidation, or (3) photo‐oxidation. UV solar exposition is a major concern in skin research, dermatology, and cosmetic science. Skin surface lipids (SSLs) and stratum corneum (SC) lipids are among the first skin components exposed to external insults such as UV radiations. Fatty acids represent a major lipid class in SSLs and SC. The aim of this paper is to study the photo‐oxidation of fatty acids under UV solar radiations using Raman spectroscopy. Vibrational spectroscopies are useful techniques to follow the LPO in its different stages of oxidation: (1) the initiation step by following the CH2 /CH3 stretching bands ratio that decreases due to the hydrogen abstraction in alpha position; (2) the propagation step where primary oxidation products are formed such as hydroperoxides, which was evaluated by following the 1165/1640 cm −1 ((δ(OH) and ν(CO))/ν(CO)) ratio that increases during oxidation process; and finally, (3) the termination step that is marked by the formation of aldehydes, alcohols, ketone, trans secondary oxidation products, and others, which was monitored by following the 1730/1640 cm −1 (ν(CO) (ald.)/ν(CO) (acid)) ratio and the trans ν(CC)/ cis ν(CC) ratio that increase indicating the formation of secondary oxidation products. To our knowledge, this work is the first to put together different spectral descriptors enabling to follow, step by step, the different modifications of free fatty acids structures during the oxidation process. Abstract : The aim of this paper was to study the photo‐oxidation of fatty acids in its different stages of oxidation by following different descriptors using vibrational spectroscopies: (1) the initiation step which process involves hydrogen abstraction in alpha position, (2) the propagation step where primary oxidation products are formed such as hydroperoxides, and finally, (3) the termination step that is marked by the formation of aldehydes, alcohols, ketone, trans secondary oxidation products, and others.